2015
DOI: 10.1080/19371918.2014.994726
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Communication of HIV Diagnosis in Rakai, Uganda

Abstract: Individuals who communicate their HIV diagnosis to sexual partners may be at increased risk of intimate partner violence (IPV). The authors examined past year self-reported IPV associated with communication of HIV diagnosis and other factors, in a sample of 679 sexually active; HIV-positive individuals age 18 to 49, who received HIV results and posttest counselling 12 months or more prior to the survey in Rakai, Uganda, using log-binomial multivariable regression. The rates of verbal and physical abuse among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Within relationships polarized with IPV, women are less likely to negotiate safer sex practices such as the use of condoms, thus increasing their susceptibility to HIV infections. For instance, evidence from East Africa indicates that most women who test HIV positive are also likely to report experiencing IPV (Hassen & Deyassa, 2013;Kairania et al, 2015;Karamagi et al, 2006;Wagman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within relationships polarized with IPV, women are less likely to negotiate safer sex practices such as the use of condoms, thus increasing their susceptibility to HIV infections. For instance, evidence from East Africa indicates that most women who test HIV positive are also likely to report experiencing IPV (Hassen & Deyassa, 2013;Kairania et al, 2015;Karamagi et al, 2006;Wagman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that vulnerabilities usually intersect and amplify each other in bidirectional ways (Winchester, 2016). In Uganda, women in marital relationships experience significantly higher rates of verbal and physical abuse than unmarried women (Kairania et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Correlates of IPV in the general population in Uganda include gender norm perceptions about violence, sociodemographic characteristics, substance abuse (especially alcohol), marital dissatisfaction, and presence of sexual problems. 9 , 11 , 16 , 22 Whereas a study conducted in Uganda by Kairania et al 23 showed that HIV-positive disclosure was associated with among women living with HIV, another study showed that disclosure was protective against IPV. 11 Other factors such as testing for HIV, HIV positive result disclosure, antiretroviral therapy use, requesting for a protective sexual encounter, low education level, and being married may lead to IPV.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Other factors such as testing for HIV, HIV positive result disclosure, antiretroviral therapy use, requesting for a protective sexual encounter, low education level, and being married may lead to IPV. 11 , 16 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…Rates of IPV may be even higher among the entire population of WLHIV (i.e., including both those who are and are not engaged in HIV care) in rural Uganda, with a recent study indicating that 72.22% of WLHIV reported at least one lifetime experience of physical, sexual, or emotional IPV ( Ogbonnaya et al, 2020). Further, researchers have found that rural Ugandan WLHIV are at higher risk of IPV than urban Ugandan WLHIV (Kairania et al, 2015).…”
Section: Introductionmentioning
confidence: 99%